Procedural Learning in Children With Developmental Coordination, Reading, and Attention Disorders. (October 2015) - Magallón, Sara; Crespo-Eguílaz, Nerea; Narbona, Juan
The aim is to assess repetition-based learning of procedures in children with developmental coordination disorder (DCD), reading disorder (RD) and attention-deficit hyperactivity disorder (ADHD). Participants included 187 children, studied in 4 groups: ( a ) DCD comorbid with RD and ADHD (DCD+RD+ADHD) (n = 30); ( b ) RD comorbid with ADHD (RD+ADHD) (n = 48); ( c ) ADHD (n = 19); and typically developing children (control group) (n = 90). Two procedural learning tasks were used: Assembly learning and Mirror drawing. Children were tested on 4 occasions for each task: 3 trials were consecutive and the fourth trial was performed after an interference task. Task performance by DCD+RD+ADHD children improved with training ( P < .05); however, the improvement was significantly lower than that achieved by the other groups (RD+ADHD, ADHD and controls) ( P < .05). In conclusion, children with DCD+RD+ADHD improve in their use of cognitive-motor procedures over a short training period. Aims of intervention in DCD+RD+ADHD should be based on individual learning abilities.